Association between frontal QRS-T angle and thrombus burden in patients with ST-elevation myocardial infarction: A single-center cross-sectional study - Azmi, Muhammad; Nasution, Ali Nafiah; Lubis, Hilfan Ade Putra; Siregar, Abdullah Afif; Habib, Faisal; Sitepu, Andika (Universitas Brawijaya, 2025)
BACKGROUND: ST-Elevation Myocardial Infarction (STEMI) is one of the leading causes of global morbidity and mortality, with burden of thrombus as an influential factor of clinical outcomes. OBJECTIVES: The purpose of this study was to evaluate the relationship between frontal QRS-T (fQRST) angle and thrombus burden in STEMI patients. METHODS: A cross-sectional study was carried out at Haji Adam Malik General Hospital, Medan, between January 2024 and July 2024. STEMI patients who underwent coronary angiography were included. The fQRST angle was measured using a 12-lead electrocardiogram (ECG), the thrombus burden was graded according to the Thrombolysis in Myocardial Infarction (TIMI) grading system. Statistical analysis included Spearman's correlation and Receiver Operating Characteristic (ROC) curve analysis. RESULTS: 108 STEMI patients were included in the study. The fQRST angle was strongly positively correlated with thrombus burden (r = 0.61–0.80, p < 0.05). Patients with more thrombus burden had larger fQRST angles compared to patients with less thrombus burden. Additionally, diabetes mellitus and symptom delay exceeding 12 hours were highly correlated with higher thrombus burden (p < 0.05), whereas infarct-related artery (IRA) location was not significantly associated (p > 0.05). ROC curve demonstrated that the fQRST angle had an AUC of 0.88 (p = 0.001) At the optimal cut-off value of 61°, the sensitivity and specificity were 88.3% and 87.5% (95% CI of 88.5%–98.2).